Role of crowdfunding and digital payment in tackling Islamic social finance institutions' challenges: a case study of direct aid society - Bioumy, Mysara; Hassan, Rusni; Al-Daihani, Meshari; Mahmoud, Ali (Integrated Publishing Association, 2025)
Purpose - this research aims to investigate the impact of using fintech tools of crowdfunding and digital payment to address the challenges of Islamic social finance institutions ISFIs including reduction of fund and lack of transparency for providing a better adoption of institutional and financial performance at ISFIs. This is through investigating a leading Islamic social finance institution in GCC countries and the Middle East region, namely Direct Aid Society based in the state of Kuwait. Methodology - The methodology is designed to capture a comprehensive understanding of the fintech tools of crowdfunding and digital payment within the Direct Aid Society and their impact on overcoming institutional challenges. Semi-structured interviews were conducted with key stakeholders, including board members, management, and staff of the Direct Aid Society. These interviews were designed to elicit detailed insights into the practical challenges faced by the institution and the role of FinTech in addressing these challenges. The collected data were analyzed using thematic analysis, a method that identifies, analyses, and reports patterns (themes) within the data. This approach enabled the researcher to distil key themes related to fintech practices and their effectiveness in tackling the challenges of Islamic social finance institutions. The in-depth face-to-face interviews furnished valuable data that was generated, rearranged and refined using the NVIVO 14 software. Findings - the research found that the use of fintech tools of crowdfunding and digital payment enhanced institutional performance, stakeholders’ protection and increased financial stability at social finance institutions especially at the institution case study. Originality/value - The research highlighted that the two selected fintech tools of crowdfunding and digital payment have considerably addressed lack of transparency, trust, disclosure and accountability as well as fund reduction. This is in the form of different actions and practices that have been deducted from the official documents and emphasized by most of the respondents